Effectiveness of Nutritional Program on Senior Person Knowledge Regarding Constipation Management at Nursing Home Centers in Al-Kut City - Mostafa Mohammad Ali Al-Fatlawi, Suad J. Mohammad (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Constipation is a clinical diagnosis based on symptoms of incomplete elimination of stool, difficulty passing stool, or both. Patients typically experience other symptoms such as hard stools, abdominal bloating, pain, and distention. Methods: A quantitative, quasi-experimental study design was carried out at two nursing home centers (Dar Al-Shhafaa government home and Basmat Al-Rahmma private nursing home) in order to determine the effectiveness of a nursing home program. Beginning on the 24th of December 2020 and ending on the 15th of January 2022, the current study will be conducted. In order to meet the study's aims, a non-probability (purposive) sample of (57) senior citizens (27) senior citizens selected for the case group and (30) senior citizens selected for the control group who were residents of a nursing home were selected. Results: Analysis of such knowledge shows that the large number of senior persons, in study group, has expressed poor level of knowledge about constipation at the pretest. Such poor level of knowledge is evidenced in all the low mean of scores on items of senior persons’ knowledge about constipation . Conclusions and recommendation :It has been emphasized in the literature that patients must spend more time seeking health-related education in order to improve their health care outcomes. The teaching must be enthusiastic, motivated, and responsive to the individual patient's needs. For individual members of the society to realize the benefits of health education, there is a need for a robust, hearty engagement between patients and health care providers .